2009
DOI: 10.1111/j.1365-2052.2009.01909.x
|View full text |Cite
|
Sign up to set email alerts
|

Ovine acyl CoA:diacylglycerol acyltransferase 1– molecular characterization, polymorphisms and association with milk traits

Abstract: The objective of this work was to characterize the complete coding region of the ovine acylCoA:diacylglycerol acyltransferase 1 (DGAT1) gene of three Italian sheep breeds: Sarda, Altamurana and Gentile di Puglia. Characterization was accomplished by direct sequencing of 8676 bp of the relevant DNA, including introns and partial 5' and 3' untranslated regions (UTRs). We detected five novel SNPs; one SNP (g.5553C>T) is located in intron 2, has similar frequencies in the three breeds and showed a negative associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 20 publications
4
36
2
Order By: Relevance
“…In sheeps and goats the DGAT1 K232A polymorphism has not been so extensively studied, although the essential role of DGAT1 in milk fat content genetic variation makes this marker an important factor for the variety of milk traits found in individuals (Scata et al, 2009;Xu et al, 2008). The previous work done by Scata et al (2009) on possible DGAT1 polymorphism revealed a single nucleotide polymorphism (SNP) in the 5'UTR of DGAT1 woth possible in luence on milk fat percent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In sheeps and goats the DGAT1 K232A polymorphism has not been so extensively studied, although the essential role of DGAT1 in milk fat content genetic variation makes this marker an important factor for the variety of milk traits found in individuals (Scata et al, 2009;Xu et al, 2008). The previous work done by Scata et al (2009) on possible DGAT1 polymorphism revealed a single nucleotide polymorphism (SNP) in the 5'UTR of DGAT1 woth possible in luence on milk fat percent.…”
Section: Introductionmentioning
confidence: 99%
“…The previous work done by Scata et al (2009) on possible DGAT1 polymorphism revealed a single nucleotide polymorphism (SNP) in the 5'UTR of DGAT1 woth possible in luence on milk fat percent.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, four alleles have been identified in the intron 12 region in New Zealand crossbred sheep by SSCP (Byun et al 2009 (Li et al 2010) and cattle (Cho et al 2008). Some variations in these genes are associated with milk fat content in sheep (Calvo et al 2004;Scata et al 2009 Identification of SNPs associated with mutton traits may not only help in improvement of the production but also provide economic gains to the rearers. Two SNPs in the GDF8 gene known to be associated with mutton quality and carcass traits in Texel (Kijas et al 2007) and New Zealand Romney sheep (Hickford et al 2010) have also been identified in Indian sheep (Arora et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The candidate gene approach involving genes with known expression of certain proteins provides genomic information that may be used in genetic improvement of sheep in the absence of resource flocks in the country. Some candidate genes like calpain (CAPN4), calpastatin (CAST), diacylglycerol acyltransferase 1 (DGAT1) and fatty acid binding protein 3 (FABP3) have been implicated in muscle development and fat metabolism (Goll et al 1992;Calvo et al 2004;Scata et al 2009). The CAPN4 is a cytosolic endopeptidase that requires calcium for catalytic activity, whereas CAST is a specific endogenous inhibitor that acts on calpain (Ma et al 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation